Behaviour of citrus pectin during its gastrointestinal digestion and fermentation in a dynamic simulator (simgi®). (1st March 2019) - Ferreira-Lazarte, Alvaro; Moreno, F. Javier; Cueva, Carolina; Gil-Sánchez, Irene; Villamiel, Mar
Highlights: A Dynamic Simulator was used for digestion and fermentation of citrus pectin. Pectin molecular weight showed minor changes after gastric and intestinal digestion. High increase of Bifidobacterium, Bacteroides and Faecalobacterium prausnitzii . High gains of short chain fatty acids during pectin fermentation in the colon stages. Abstract: The behaviour of citrus pectin during digestion and its potential prebiotic properties were examined using a Dynamic Gastrointestinal Simulator (simgi®) model for the human gut, which simulates processes in the stomach, small intestine, ascending, transverse and descending colon. A remarkable non-digestibility of pectin in the upper gastrointestinal tract was observed by HPLC-ELSD analysis, where ∼88% of citrus pectin remained intact during its transit through the stomach and small intestine. Fermentation of pectin stimulated the growth of beneficial bacteria such as Bifidobacterium spp, Bacteroides spp and Faecalobacterium prausnitzii. High increases of short-chain fatty acids (SCFA) were observed, especially in acetate and butyrate concentration due to direct fermentation of pectin or by cross-feeding interaction between bacteria. This is the first study on the digestibility and fermentation of pectin carried out in a complex dynamic gastrointestinal simulator, being of special relevance the results obtained for F. prausnitzii.